2021
DOI: 10.1371/journal.pone.0246440
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preovulatory versus midluteal serum progesterone level on live birth rates during fresh embryo transfer

Abstract: Background Conflicting evidence still prevails concerning the effect of preovulatory elevated progesterone (EP4) on reproductive outcomes in fresh embryo transfer (ET). However, few studies have analyzed the effect of EP4 on the likelihood of pregnancy using multivariate regression approach. The potential confounding factors tested in these studies were limited to either patient’s characteristics or to stimulation related parameters. Yet, several studies have shown that postovulatory parameters such as midlute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The progesterone threshold ranged from 0.9ng/ml to 2.0ng/ml. Twenty-one studies reported using D3 embryos [14][15][16][17][18][19][20]22,23,27,30,32,34,36,40,[45][46][47][48]50,56 , four studies reported using D5 embryos 31,33,37,54 , eighteen studies reported using both D3 and D5 embryos 21,24,25,29,38,39,[41][42][43][44]49,[51][52][53]55 and three studies did not specify the stages of embryo used 26,28,35 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The progesterone threshold ranged from 0.9ng/ml to 2.0ng/ml. Twenty-one studies reported using D3 embryos [14][15][16][17][18][19][20]22,23,27,30,32,34,36,40,[45][46][47][48]50,56 , four studies reported using D5 embryos 31,33,37,54 , eighteen studies reported using both D3 and D5 embryos 21,24,25,29,38,39,[41][42][43][44]49,[51][52][53]55 and three studies did not specify the stages of embryo used 26,28,35 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The main characteristics of the included studies are reported in Supplementary Table 1. The included women were recruited during their first or second cycle (19)(20)(21)(22)(23), all of them (24)(25)(26)(27)(28)(29)(30) or not specified (11,14,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Studies concerned either autologous cycles (13, 14, 19, 21, 22, 25, 27, 29-32, 36, 38-43, 45, 47), oocyte donation (20,44) or not specified (11, 21, 23, 26, 28, 33-35, 37, 46).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Studies concerned either autologous cycles (13, 14, 19, 21, 22, 25, 27, 29-32, 36, 38-43, 45, 47), oocyte donation (20,44) or not specified (11, 21, 23, 26, 28, 33-35, 37, 46). Studies included single-embryo transfers (11,13,22,28,33,35,40,41), single-or double-embryo transfers (19,20,26,27,30,31,34,37,46), transfers of two to three embryos (24), transfers of three to four embryos (38,39,44) and not reported (14,21,23,25,29,36,43,45,47). Transferred embryos were cleaved embryos (21,24,27,29,34,39), blastocyst embryos (11,13,14,19,20,22,23,26,…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that LFPE can reduce the pregnancy rate after embryo transfer in fresh cycles by affecting the quality of oocytes/embryos and endometrial receptivity (4)(5)(6). Conversely, another study revealed no correlation between LFPE length and pregnancy outcomes (7,8).…”
Section: Introductionmentioning
confidence: 99%